Value from faecal sludge and municipal organic waste: fertilizer cum soil conditioner in Ghana - Impraim, Robert; Nikiema, Josiane; Cofie, Olufunke O.; Rao, Krishna (2014)
Ghana is confronted with waste management challenges. with 20-40% uncollected solid waste in most cities. Also. large volumes of faecal sludge are discharged untreated into the environment. Although these wastes pose serious environmental concerns, they also contain nutrients and organic matter essential for improving soil agricultural productivity. The International Water Management Institute (IWMI), since 2001. has researched into nutrient and organic matter recovery from faecal sludge and organic solid waste in Ghana and some Asian countries such as India, Sri Lanka or Bangladesh. This has led to the production of various formulations of faecal sludge based compost (with "Fortifer" as a generic 'brand '), both in the form ofpellets and powders, and specifically an ongoing project aiming at producing and commercializing the Fortifer in Ghana through a Public Private Partnership. This paper presents a summary of Fortifer technology, project objectives as well as lessons learnt during its implementation.